ORGANIZATIONAL LEADERSHIP IN CORPORATE CHANGE AND ITS EFFECT ON PERFORMANCE OF COMMERCIAL BANKS IN KENYA - Paul Muteti Kitemu; Dr. Anne Sang; Dr. Anita Wachira (Galaxy International Interdisciplinary Research Journal, 2024)
Commercial banks in Kenya have been embracing corporate changes as a way of enhancing their continued performance in the over-dynamic operating environment. The success of this corporate change has however had mixed outcomes as some banks are yet to gain significant performance even after the changes. Moreover, the place of employees in the corporate changes has not been adequately addressed. It is against this background that this study sought to assess the influence of organizational leadership as an aspect of corporate change on organizational performance of commercial banks in Kenya. The study was anchored on contingency theory of leadership, and utilized a descriptive cross-sectional research design. The target population was 29,600 employees drawn from the 39 licensed commercial banks in Kenya. A sample of 394 respondents estimated using Yamane’s sampling formula and identified using stratified random sampling technique was surveyed. A questionnaire was used to collect primary data which was analysed through SPSS. The findings revealed that organizational change as an aspect of corporate change had a significant impact on the performance of commercial banks in Kenya (β = 0.613; P= 0.000<0.05). The study concluded that organizational leadership exemplified during corporate change was integral in determining the success of the change towards enhancing banks’ performance. It is recommended that the banking managers particularly the tope leadership should provide close leadership during corporate change where they engage the employees, lead by example and show strategic direction for the changes to be effective.